2016
DOI: 10.5194/gi-5-151-2016
|View full text |Cite
|
Sign up to set email alerts
|

Practical considerations for enhanced-resolution coil-wrapped distributed temperature sensing

Abstract: Abstract. Fibre optic distributed temperature sensing (DTS) is widely applied in Earth sciences. Many applications require a spatial resolution higher than that provided by the DTS instrument. Measurements at these higher resolutions can be achieved with a fibre optic cable helically wrapped on a cylinder. The effect of the probe construction, such as its material, shape, and diameter, on the performance has been poorly understood. In this article, we study data sets obtained from a laboratory experiment using… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 24 publications
(53 reference statements)
1
23
0
Order By: Relevance
“…7). However, we found that the maximum modeled conduction error was always smaller than temperature artifacts caused by the acrylic glass rings supporting the reinforcing fabric, which amounted to approximately 2.5 K. For a fiber cable coiled around a perforated PVC tube, Hilgersom et al (2016a) reported a mean measured conduction error of −0.4 and 0.1 K with extremes up to 0.7 K during a fog event. One must recall that in this study the conduction error was defined as the difference between the fiber temperature for open air and fiber temperature at the perforated PVC tube.…”
Section: Evaluation Of the Radiation Error And Artifacts Caused By Thmentioning
confidence: 94%
See 4 more Smart Citations
“…7). However, we found that the maximum modeled conduction error was always smaller than temperature artifacts caused by the acrylic glass rings supporting the reinforcing fabric, which amounted to approximately 2.5 K. For a fiber cable coiled around a perforated PVC tube, Hilgersom et al (2016a) reported a mean measured conduction error of −0.4 and 0.1 K with extremes up to 0.7 K during a fog event. One must recall that in this study the conduction error was defined as the difference between the fiber temperature for open air and fiber temperature at the perforated PVC tube.…”
Section: Evaluation Of the Radiation Error And Artifacts Caused By Thmentioning
confidence: 94%
“…fiber-optic cable, which is limited by the along-fiber resolution of the DTS instrument to several tens of centimeters. To overcome this issue, several studies have used a support structure for helically coiling the fiber-optic cable and thus enhancing the spatial resolution up to the millimeter scale in one dimension (Selker et al, 2006;Suárez et al, 2011;Vercauteren et al, 2011;Van Emmerik et al, 2013;Euser et al, 2014;Hilgersom et al, 2016a). Recently, this idea was expanded to all three dimensions by spanning horizontal nets of fiber-optic cable across a cage (Hilgersom et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations